IDENTITY DISCOURSE IN BALIKUI AND AIDS SHORT STORY BY PUTU WIJAYA - Nuke Affandy, Ali (TELL - US JOURNAL, 2022)
The role of literature today is not only as an imaginative work but as an expression of social, cultural and political criticism. One of the writers who is famous for voicing his criticism of the social phenomena that occur in Indonesia is Putu Wijaya. Two of his short stories that discuss cultural values are Balikui and Aids. The focus of this research is on the identity that appears in the characters in the two short stories by utilizing Michael Foucault's theory of discourse analysis. The results of this study indicate that in the Balikui short story, the identity of the character Wayan cannot be melted, even though he is in America for a few weeks as in disciplining time. In the short story Aids, it shows the existence of Indonesian cultural identity that corruption is a plague that is more dangerous than Aids.